The Role of civil society organizations in poverty reduction in Myanmar - AUNG, May Thazin (KDI School, 2016)
The study investigated the role of civil society organizations in the poverty reduction development process in Myanmar. This paper mainly focused on the relationship between civil society organizations and government bodies in terms of the implementation of different state programs that related to poverty reduction and rural development programmes. A conducted survey and an in-depth interview with the experts and civil society organizations help us to analyze the level of cooperation between government and civil society organizations, and also the role of civil society in this area. The study finds out some strength, weakness, opportunities and challenges that come from environmental factors and an unequal allocation of public services; however, through this paper we also learn about some best practices in terms of CSOs and government partnership, which can be used as a catalyst in the improvement of the process. Delightful all these findings and the successful practices of the paper indicates recommendations that can be valuable for government institutions and civil society organizations to improve their cooperation, as well as recommendations for donors.
Thesis(Master) --KDI School:Master of Public Policy,2016